LYMPH NODE REGULATORY T-CELL IN Muc2-/- MICE WITH HELICOBACTER SPP. - K. M. Achasova; O. V. Gvozdeva; E. N. Kozhevnikova; E. A. Litvinova (Медицинская иммунология, 2021)
The immune processes associated with the formation of resistance to pathogens in the intestine depend on the microbiome. The maintenance of homeostasis in the intestine is provided by regulatory T-cells. In inflammatory bowel disease (IBD), both a disturbance of the T-regulatory function and changes in microflora are observed. Aggravation of the disease is accompanied by various infections. However, pathobionts such as Helicobacter spp., can affect regulatory T-cells. One of the genetic models for studying IBD is Muc2 knockout mice. In these mice, as in humans with IBD, intestinal epithelial and immune cells closely interact with the microflora. It is believed that the immune cells of the lymph nodes Muc2-/- mice are sensitive to changes in the microflora formed in them. In this study, the effect of Helicobacter spp. on the number and percentage of different types of leukocytes and T regulatory cells in the mesenteric lymph nodes of Muc2-/- mice was studied. The number of CD45+CD19+, CD45+CD3+, CD45+CD3+CD4+, CD45+CD3+CD8+-cells in the mesenteric lymph nodes of Muc2-/- mice was significantly higher to compare with wild-type Muc2+/+ mice. However, the presence of infection in Muc2-/- mice canceled the increase in the number of CD45+CD19+, CD45+CD3+, CD45+CD3+CD4+, CD45+CD3+CD8+-cells. In wild-type Muc2+/+ mice, infection had no significant effect on cells in mesenteric lymph nodes. This change in the decrease in immune cells in the mesenteric lymph nodes under the Helicobacter spp. may be associated with the activation of regulatory T-cells. Indeed, it has been shown that the presence of a congenital Helicobacter spp. infection increased of the number of regulatory T-cells (CD45+CD4+CD25+FoxP3+) in the mesenteric lymph nodes. Well known that regulatory T-cells mediate anti-inflammatory responses in the gut. Thus, an increase in regulatory T-cells promotes a decrease in all types of immune cells in the mesenteric lymph nodes of Muc2-/- mice infected with Helicobacter spp. It could provide an improvement in the vital functions of these mice and possibly reduces inflammatory responses in the intestine. This may indicate that some congenital pathobionts activate of the regulatory mechanisms of immunity and, thereby, have a beneficial effect on the host.